Structural performance of 3D-printed composites under various loads and environmental conditions. (November 2020) - Khosravani, Mohammad Reza; Zolfagharian, Ali; Jennings, Matt; Reinicke, Tamara
Abstract: Sandwich-structured composites are in high demand in various industries, and additive manufacturing has proven its ability to meet this demand. As a result of the advances in three-dimensional (3D) printing techniques, 3D-printed polymers have received considerable attention in fabrication of sandwich structures with complex geometries. This paper is concerned with design, manufacturing, and analysis of the 3D-printed sandwich-structured components which experienced various loadings and environmental conditions. The core structure plays a major role in the in-plane behavior of lattice composites, therefore in this study, sandwich specimens with two types of core topologies made of two common and similar 3D printing filaments, acrylonitrile butadiene styrene (ABS) and acrylonitrile styrene acrylate (ASA), were manufactured. Based on the applications of sandwich-structured parts, they might experience different temperatures in their service life. In order to determine effects of thermal environment, we conducted accelerated thermal aging within temperatures of 22-60  ° C, which is below glass temperature of the examined materials. Based on a series of three-point bending tests, the failure behavior of the original and aged components are determined, and the effects of temperature change on the bending behavior of 3D-printed sandwich parts are discussed. The experimental practice revealed that ASA with honeycomb core specimens indicated highest stability under bending load after thermal aging. The current study sheds lights on durability of 3D-printed sandwich structural elements, and the obtained results demonstrate feasibility of 3D printing technology in fabrication of thermal-stable sandwich structures. Highlights: Fabrication of 3D-printed sandwich-structured components. Conducting accelerated thermal aging on produced specimens. Performing a series of three-point bending tests on the fabricated sandwich parts. Failure analysis and discussion on the fracture behavior of aged and unaged 3D-printed specimens.